A compact four port MIMO antenna for millimeterwave applications - Mohini Narendra Naik; Hasanali Gulamali Virani (Bulletin of Electrical Engineering and Informatics, 2022)
A novel compact microstrip MIMO antenna with high isolation and low envelope correction coefficient has been proposed and presented in this paper. The proposed antenna is compact in size with 3.22x4.86 mm2, operating over the frequency band of 60GHz. The MIMO antennas have been designed andsimulated using electromagnetic design and verification platformIE3DTM. Two ports MIMO antenna with the size of 3.22x1.93 mm2 resonates at 58.1 GHz covering a band of 57-59.3 GHz, with the bandwidth of 2.3 GHz, gain of 5.2 dBi, and directivity of 8.67 dBi. It also provides aninput reflection coefficient of -18.41 dB with isolation of -19.98 dB. Proposed four port MIMO antenna resonates at 58 GHz covering a range of 56.9 GHz to 59.2 GHz, with a bandwidth of 2.3 GHz, gain of 5.44 dBi, and the directivity of 9.75dBi. It provides goodisolationranging from -19 dB to -30 dB with input reflection coefficient of -18.09 dB. The envelope correlation coefficient (ECC) of the proposed four-port MIMO antenna is below 0.06 in far-field radiation characteristics. The proposed MIMO antenna has been analyzed for its diversity performance in terms of ECC, mean effective gain, and diversity gain.